Preparing Nepal’s Vision for 2050 in Water and Energy - Thanju, Jeewan P (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
DOI: http://dx.doi.org/10.3126/hn.v13i0.11223 HYDRO NEPAL Journal of Water, Energy and Environment Issue No. 13, July 2013 Page: 70-71